ANALYSIS OF THE LAYOUT OF THE FINISHED GOODS WAREHOUSE USING THE SHARED STORAGE METHOD TO INCREASE STORAGE EFFECTIVENESS IN PT. NCS LOGISTIC LINK - Putri Shima; Akhmad Syakhroni (Journal of Applied Science and Technology, 2021)
PT NCS LOGISTIC LINK is a Transportation Management Service company or commonly called Freight Forwarding.  PT.  NCS is also engaged in the rental of Warehouses. In the Warehouse at PT NCS LOGISTIC LINK, there is a problem with the layout of the storage of goods in the Warehouse which is still not optimal because the cost of Material Handling in the company is still high and also PT NCS LOGISTIC LINK, a company that manages warehouse rental for companies  manufacture.  The problems faced by PT NCS LOGISTIC LINK today are the problems that are often faced is the handling of incoming and outgoing goods in the company's warehouse, the company still does not have a defined system, so that the placement of goods in the warehouse is not neatly arranged so that the warehouse seems narrow.  Likewise, the warehouse line or line layout is not clear, the placement of finished goods for both export and local products is placed in one location with the material (Completely Knock Down / CKD) in one warehouse location, there is no barrier between the goods belonging to one customer and another.  other things, goods are placed to close the road area or forklift lanes and warehouse doors, and goods that have entered earlier are closed with new incoming goods, thus hampering the process of handling goods.  With limited storage space, companies are required to use space effectively and efficiently so that storage activities are not hampered and can find the best layout that is more effective and efficient and does not hamper the delivery process.  The method used in warehousing management is a shared storage approach in which the products that have the most shipping frequency and the ones that frequently go in and out are brought close to the entrance to minimize the distance of material handling movement.  The results of the shared storage approach can minimize the material handling distance of the proposed layout is 1386 m, while the previous condition, the initial layout distance was 1900 m. Has a total range of 514 meters of total mileage. This means that the layout of the proposal could shorten the mileage through which warehouse workers take goods.